Effect of laser hardening on the mechanical, tribological and corrosion properties of low alloy steels (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
This research focuses on studying the mechanical, tribological, and corrosion behaviors of alloy steels: AISI 4340, AISI 5140, and AISI 8620 by laser hardening, respectively. In light of the tests which have been carried out meticulously, it is concluded that the optimum laser hardening parameter for all steel grades is 4 mm/s scanning speed and 1300 °C surface temperature. Micro-structural changes, Vickers hardness as mechanical properties, and tribological properties with reciprocating wear tests were carried out.  Furthermore, corrosion tests were conducted. The test results reveal that the maximum hardness is achieved 50-300 μm below the surface for all laser-hardened steels. Additionally, this study demonstrates that the wear resistance of steel is enhanced by the implementation of laser hardening. This study also determines that laser hardening has a positive impact on lifting the corrosion resistance behavior of AISI 4340 steel. In contrast, the corrosion resistance properties of AISI 8620 steel were reduced nearly by 54.17%.
Keywords: Laser Hardening, Alloy Steels, Mechanical Properties, Wear Resistance, Corrosion